2021
DOI: 10.5811/westjem.2020.10.48008
|View full text |Cite
|
Sign up to set email alerts
|

Point-of-care Ultrasound to Evaluate Breast Pathology in the Emergency Department

Abstract: Introduction: As physician-performed point-of-care ultrasound (POCUS) becomes more prevalent in the evaluation of patients presenting with various complaints in the emergency department (ED), one application that is significantly less used is breast ultrasound. This study evaluates the utility of POCUS for the assessment of patients with breast complaints who present to the ED and the impact of POCUS on medical decision-making and patient management in the ED. Methods: This was a retrospective review of ED pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Point-of-care ultrasound (POCUS) is a diagnostic imaging modality that can be used to evaluate various complaints in the ED. [6] POCUS has emerged as a quick and reliable modality for bedside diagnosis of skin and soft tissue infections (SSTIs). [6][7][8][9] Due to the absence of radiation, real time image acquisition, and relatively low cost of imaging, there are significant advantages to use POCUS in the diagnosis of SSTIs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point-of-care ultrasound (POCUS) is a diagnostic imaging modality that can be used to evaluate various complaints in the ED. [6] POCUS has emerged as a quick and reliable modality for bedside diagnosis of skin and soft tissue infections (SSTIs). [6][7][8][9] Due to the absence of radiation, real time image acquisition, and relatively low cost of imaging, there are significant advantages to use POCUS in the diagnosis of SSTIs.…”
Section: Introductionmentioning
confidence: 99%
“…[6] POCUS has emerged as a quick and reliable modality for bedside diagnosis of skin and soft tissue infections (SSTIs). [6][7][8][9] Due to the absence of radiation, real time image acquisition, and relatively low cost of imaging, there are significant advantages to use POCUS in the diagnosis of SSTIs. [9][10] Previous studies have demonstrated that POCUS can improve diagnostic accuracy and alter management plans in patients with SSTIs.…”
Section: Introductionmentioning
confidence: 99%